Ralph Locke, Musical Exoticism: Images and Reflections (2009) - Zon, Bennett (Journal of the Society for Musicology in Ireland, 2012)
A review of Ralph Locke, Musical Exoticism: Images and Reflections (Cambridge: Cambridge University Press, 2009), ISBN 978-0-5213-4955-0.